Discrete-time Holling type II models with Allee and refuge effects - Unal Ufuktepe; Burcin Kulahcioglu (E-Journal of Analysis and Applied Mathematics)
The discrete-time Holling type II prey-predator models with the refuge and Allee effects are formulated and studied. The existence of fixed points and their stabilities are investigated for both hyperbolic and non-hyperbolic cases. Numerical simulations are conducted to demonstrate the theoretical results.